The antifungal peptide AnAFP from Aspergillus niger promotes nutrient mobilization through autophagic recycling during asexual development - Starke, Stephan; Velleman, Laura; Dobbert, Birgit; Seibert, Luis; Witte, Jordi; Jung, Sascha; Meyer, Vera (Frontiers in Microbiology, 2025)
Antifungal peptides are promising drug candidates to fight fungal infections in the clinics and agriculture. However, recent data suggest that antifungal peptides might also play a role within their own producing organism to survive nutrient limiting conditions. We have therefore studied the function of the antifungal AnAFP in Aspergillus niger in more detail. To achieve this, we established a Tet-on controlled anafp expression system, which allowed us to study a null and an overexpression phenotype in the same isolate. We observed that increased intracellular AnAFP expression reduces growth of A. niger and prematurely activates autophagy. Comparative transcriptome analyses of glucose-starving mycelium demonstrated that increased anafp expression strongly impacts expression of genes important for cell wall integrity and remodeling, as well as genes with a predicted function in metabolism and transport of carbohydrates, proteins, and lipids. Notably, genes encoding regulators of conidiophore development such as flbC and flbD became induced upon anafp overexpression. Fluorescent analyses of a Tet-on driven AnAFP::eGFP fusion protein congruently unraveled that AnAFP localizes to cell walls and septa of A. niger. Moreover, AnAFP::eGFP expression is spatially restricted to selected compartments only and affected cells displayed a sudden reduction in hyphal diameter. From these data we conclude that AnAFP is important to drive vegetative growth and sporulation in A. niger during nutrient limitation through autophagic recycling. We predict that AnAFP drives nutrient mobilization through selective cell lysis to ensure the survival of the whole colony during phases of starvation.